Visual-auditory spatial processing in auditory cortical neurons. - Bizley, J; King, A (2008)
Neurons responsive to visual stimulation have now been described in the auditory cortex of various species, but their functions are largely unknown. Here we investigate the auditory and visual spatial sensitivity of neurons recorded in 5 different primary and non-primary auditory cortical areas of the ferret. We quantified the spatial tuning of neurons by measuring the responses to stimuli presented across a range of azimuthal positions and calculating the mutual information (MI) between the neural responses and the location of the stimuli that elicited them. MI estimates of spatial tuning were calculated for unisensory visual, unisensory auditory and for spatially and temporally coincident auditory-visual stimulation. The majority of visually responsive units conveyed significant information about light-source location, whereas, over a corresponding region of space, acoustically responsive units generally transmitted less information about sound-source location. Spatial sensitivity for visual, auditory and bisensory stimulation was highest in the anterior dorsal field, the auditory area previously shown to be innervated by a region of extrastriate visual cortex thought to be concerned primarily with spatial processing, whereas the posterior pseudosylvian field and posterior suprasylvian field, whose principal visual input arises from cortical areas that appear to be part of the 'what' processing stream, conveyed less information about stimulus location. In some neurons, pairing visual and auditory stimuli led to an increase in the spatial information available relative to the most effective unisensory stimulus, whereas, in a smaller subpopulation, combined stimulation decreased the spatial MI. These data suggest that visual inputs to auditory cortex can enhance spatial processing in the presence of multisensory cues and could therefore potentially underlie visual influences on auditory localization.